Impacts on Meteorological Parameters and Pollutants by Aerosol Direct Radiative Effect Over Tianjin, China - Hao, Jian; Cai, Ziying; Han, Suqin; Ma, Gengxue; Zhang, Min; Qiu, Xiaobin (Frontiers in Environmental Science, 2022)
The direct radiative effect (DRE) of anthropogenic aerosols on meteorological elements and pollutants over Tianjin, China was investigated using a fully coupled meteorology-chemistry model [Weather Research and Forecasting (WRF) Model coupled with Chemistry (WRF-Chem)] for the entire year of 2021. The results showed that the ground solar radiation decreased from 208.86 W/m2 to 194.52 W/m2 due to DRE, the percentage of the reduction was 6.79%. The decline in ground solar radiation resulted in decrease of temperature, boundary layer height and visibility in percentage of 0.90%, 1.13% and 6.01%, respectively, and increment of relative humidity in percentage of 0.80%. The changes of meteorological parameters changed the diffuse conditions of pollutants, lead to an increment of PM2.5. The higher concentration of pollutants leads to stronger DRE, the percentages of changes caused by DRE in polluted days are higher than those in clean days. The DER influence on pollutants can be summarized as weather → aerosol → weather → air quality circulation mechanism. The DRE had more severe influence on weather and pollutants in foggy days.